PERGESERAN PEMAKNAAN RITUAL ‘MERTI DUSUN’; STUDI ATAS RITUAL WARGA DUSUN CELENGAN, TUNTANG, SEMARANG - M. Aly Haedar (UIN Raden Mas Said Surakarta, 2016)
Ritual ‘Merti Dusun’ has been practiced by people of Celengan, far before Islam becomes the part of their daily lives. After the coming of Islam to Java Island, this ritual experienced acculturation with Islamic culture. The ritual which initially was meant to refuse disaster and ask of benediction to The Creator (God), by giving offerings to certain place and request permit to the Prophet, and Danyang of certain place, has shifted in the term of its meaning. This study found out that this ‘merti dusun’ ritual has experienced meaning shift, either individually or communally. There are altering meanings: from addressing the ritual and prayer to danyang shifted to all of Islamic missionaries; to an assumption that the ritual has deviated from the religious teaching; and there is also person who simply assumed it just as social obligation.